2008
DOI: 10.1007/s10620-008-0325-8
|View full text |Cite
|
Sign up to set email alerts
|

Impairment by 5-Fluorouracil of the Healing of Gastric Lesions in Rats: Effect of Lafutidine, a Histamine H2 Receptor Antagonist, Mediated by Capsaicin-Sensitive Afferent Neurons

Abstract: We investigated the influence of 5-fluorouracil (5-FU), an anti-tumor agent, on the healing of gastric lesions generated by 0.6 M HCl in rats and the effect of lafutidine, a histamine H(2) receptor antagonist, on the impaired healing. Animals fasted for 18 h were given 1 ml of 0.6 M HCl p.o., fed normally from 1 h later, and killed 1-96 h thereafter. 5-FU was given i.v. twice, 1 h and 24 h after the HCl. The gastric lesions healed spontaneously within 96 h. Although it decreased acid secretion, 5-FU markedly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…However, lafutidine by itself does not have any direct effects on cell migration or proliferation. An earlier study demonstrated that lafutidine does not influence the impaired healing of epithelial wounds in RGM1 cells under in vitro conditions without neuronal innervations (Murashima et al, 2009), again confirming the importance of sensory neurons in the healing-promoting action of this agent. Several studies show that luminal lafutidine stimulates capsaicin-sensitive afferent nerves via presumably direct diffusion rather than after its absorption from intestine followed by via circulation, suggesting the rapid local diffusion reaching to the afferents before H 2 -receptor blockade from the circulation (Onodera et al, 1999b;Nagahama et al, 2003).…”
Section: Mechanisms Of Gastroprotective Actionsmentioning
confidence: 61%
See 2 more Smart Citations
“…However, lafutidine by itself does not have any direct effects on cell migration or proliferation. An earlier study demonstrated that lafutidine does not influence the impaired healing of epithelial wounds in RGM1 cells under in vitro conditions without neuronal innervations (Murashima et al, 2009), again confirming the importance of sensory neurons in the healing-promoting action of this agent. Several studies show that luminal lafutidine stimulates capsaicin-sensitive afferent nerves via presumably direct diffusion rather than after its absorption from intestine followed by via circulation, suggesting the rapid local diffusion reaching to the afferents before H 2 -receptor blockade from the circulation (Onodera et al, 1999b;Nagahama et al, 2003).…”
Section: Mechanisms Of Gastroprotective Actionsmentioning
confidence: 61%
“…Cimetidine and ranitidine belong to the conventional group characterized by a fivemembered aromatic ring. Recently, some of the newer H 2 -blockers (so-called secondgeneration H 2 -blockers) have been reported to promote the gastric mucosal defense mechanisms (Fukushima et al, 2006;Harada et al, 2007;Marazova et al 1998;Murashima et al, 2009;Saegusa et al, 2008;Ichikawa et al, 2009a). Second-generation H 2 -blockers contain a six-membered aromatic ring, instead of a five-membered heterocyclic ring.…”
Section: Structure Of Second-generation H 2 -Blockersmentioning
confidence: 99%
See 1 more Smart Citation